LEDAKAN BARU PENDIDIKAN ISLAM: Bagaimana Kecerdasan Siswa Disiapkan Memasuki Era Society 5.0 - Maya Novita Sari; Destri Fitriana (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
The intelligence of students in the contemporary era is no longer traditionally measured from cognitive achievement alone. The development of research on children's intelligence states that the ability to multi-intelligence is currently needed in the era of Society 5.0. Because at this time one's intelligence is required to be able to balance the development of an increasingly fast era and changing situations that are uncertain. In Islamic education, human intelligence is based on divine values ​​contained in the Qur'an as the core principle of intelligence. Because the core of Islamic teachings is aimed at developing one's potential as well as leading to an optimal direction. This study is a library research, data is collected from various literatures, then the data is processed by synthesizing various relationships between existing data and analyzed by descriptive analysis. The results of the study indicate that in order to increase the intelligence of students in the 5.0 era, it is necessary to strengthen contemporary learning models that are relevant in Islamic education. This learning model increases critical-religious reasoning which becomes the capital for students not only to think rationally but also to strengthen the awareness of divinity.